Antenna Designs for 5G/IoT and Space Applications - Tubbal, Faisel; Matekovits, Ladislau; Raad, Raad (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is intended to shed some light on recent advances in antenna design for these new emerging applications and identify further research areas in this exciting field of communications technologies. Considering the specificity of the operational environment, e.g., huge distance, moving support (satellite), huge temperature drift, small dimension with respect to the distance, etc, antennas, are the fundamental device allowing to maintain a constant interoperability between ground station and satellite, or different satellites. High gain, stable (in temperature, and time) performances, long lifecycle are some of the requirements that necessitates special attention with respect to standard designs. The chapters of this book discuss various aspects of the above-mentioned list presenting the view of the authors. Some of the contributors are working strictly in the field (space), so they have a very targeted view on the subjects, while others with a more academic background, proposes futuristic solutions. We hope that interested reader, will find a fertile source of information, that combined with their interest/background will allow efficiently exploiting the combination of these two perspectives.